Formação de professores para educação de jovens e adultos : um estudo sobre o curriculo do curso de Pedagogia em Sergipe - Silva, Jéssica Fernanda França (2016)
This research is a critical study, focused on the issue of teacher training. One of the problems observed in the course of Education Degree was the weakness of the curriculum in the content of education for youth and adults, usually distributed in one compulsory subject, and other subjects and optional disciplines that could make an argument that considers the issue of adult education and they do not. From this we did the following question: What ideas are being given priority in the curriculum of Pedagogy for performance in adult education? To answer this question from some criteria we chose to analyze the initial teacher training course in pedagogy degree two institutions of higher education in Sergipe (one public and one private institution). Based on the proposed text of the laws, Law of Guidelines and Bases of National Education (LDB 1996), National Education Plan (PNE 2014) and National Curriculum Guidelines for youth and adults (2000) and studies Haddad (2000), Di Pierro (2000), Soares (2006), Arroyo (2006) among others, points us to the importance of training to respond to the specificity of adult education. To achieve the objectives, we opted for a qualitative approach, and as material for data collection for documentation and analysis of semi-structured interviews. We rely on historical dialectic materialism, as this allows us to obtain the contradictions and the explanations of the social relations of reality from an overall perspective. The data show that the challenge is the Faculty of Education in relation to the initial training activities in adult education, the importance of rescuing the links between work and education, as these conceptions corroborate an understanding, but that kind of extensive education, service and for whom the teacher of adult education, as well as understanding of relationships and social practices within this capitalist model of society is inserted. It also showed that the course program with a single discipline in the compulsory curriculum component is insufficient in relation to give an initial depth training regarding adult education, and the need for greater dialogue between the disciplines of the course, as these discussions bring relevant and meaningful relationships with the issue of adult education. Therefore, the analysis of the data led us to confirm our initial hypothesis that there are deficiencies in the approaches of the disciplines that deal with specific depths of AYE. And these deficiencies are widespread, we lack deeper theoretical, not only from a pedagogical point of view, but especially the relationship between society and education, which requires a political position in the face of contradictions.